Karmic Songs for voice, theremin, and piano quartet (2023) - Boondiskulchok, Prach (2023)
Duration 20’;Publication pending in May 2024;Commissioned by Camerata Variabile;World premiere: Musikschule Konservatorium, Zürich, Switzerland, 18 April 2023
Abstract:Karmic Songs is a set of reflections on the concepts of the soul, ghosts, and karma, inspired by Thaifolktales and Theravadin Buddhist thoughts. The first song sets Mary Oliver’s poem Bone, where, in searchfor what the soul might be, the narrator finds an ear bone of a whale and contemplates on whether thesoul might look like this—the ear bone is crucial to the whale’s ability to navigate. This resonates withhow it is also the most crucial part for musicians, and is, in a way, like their “souls”. The second and thirdsongs set an assemblage of texts from many sources, from old Buddhist Suttas to contemporary poemswhich I have borrowed and threaded together. Telling the story of a Preta or “hungry ghost”, one of theghosts commonly used in Thailand to scare children from misbehaving, myself affected. In this song theghost itself warns us, the living, of our greed and endless “wanting more and more of the earth”. The finalsong is a prayer of hope, calling upon the “miracles of honesty and truth to keep the sky from falling.”
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850